Plant foods, dietary fibre and risk of ischaemic heart disease in the European Prospective Investigation into Cancer and Nutrition (EPIC) cohort. (27th November 2020) - Perez-Cornago, Aurora; Crowe, Francesca L; Appleby, Paul N; Bradbury, Kathryn E; Wood, Angela M; Jakobsen, Marianne Uhre; Johnson, Laura; Sacerdote, Carlotta; Steur, Marinka; Weiderpass, Elisabete; Würtz, Anne Mette L; Kühn, Tilman; et al.
Abstract: Background: Epidemiological evidence indicates that diets rich in plant foods are associated with a lower risk of ischaemic heart disease (IHD), but there is sparse information on fruit and vegetable subtypes and sources of dietary fibre. This study examined the associations of major plant foods, their subtypes and dietary fibre with risk of IHD in the European Prospective Investigation into Cancer and Nutrition (EPIC). Methods: We conducted a prospective analysis of 490 311 men and women without a history of myocardial infarction or stroke at recruitment (12.6 years of follow-up, n cases = 8504), in 10 European countries. Dietary intake was assessed using validated questionnaires, calibrated with 24-h recalls. Multivariable Cox regressions were used to estimate hazard ratios (HR) of IHD. Results: There was a lower risk of IHD with a higher intake of fruit and vegetables combined [HR per 200 g/day higher intake 0.94, 95% confidence interval (CI): 0.90–0.99, P -trend   =   0.009], and with total fruits (per 100 g/day 0.97, 0.95–1.00, P- trend   =   0.021). There was no evidence for a reduced risk for fruit subtypes, except for bananas. Risk was lower with higher intakes of nuts and seeds (per 10 g/day 0.90, 0.82–0.98, P- trend   =   0.020), total fibre (per 10 g/day 0.91, 0.85–0.98, P- trend   =   0.015), fruit and vegetable fibre (per 4 g/day 0.95, 0.91–0.99, P- trend   =   0.022) and fruit fibre (per 2 g/day 0.97, 0.95–1.00, P- trend   =   0.045). No associations were observed between vegetables, vegetables subtypes, legumes, cereals and IHD risk. Conclusions: In this large prospective study, we found some small inverse associations between plant foods and IHD risk, with fruit and vegetables combined being the most strongly inversely associated with risk. Whether these small associations are causal remains unclear.